Evaluation of efficient microorganisms in the tomato seedling production (Solanum lycopersicum L.) - Calero, Alexander H. [UNESP]; Quintero R, Elieni; Perez D, Yanery; Olivera, Dilier [UNESP]; Pena, Kolima C.; Castro L, Ivan; Jimenez H, Janet (Univ Narino, 2019)
The main problems of the production of tomato seedlings in the tropical regions reside mainly by the affectation by climatic factors and the low use of biofertilizers, for which, it is important to look for efficient alternatives of biofertilizers management in these regions that increases the rationality and sustainability. The objective of the work was to evaluate different application forms of efficient microorganisms in the tomato seedlings production. The randomized block design was used, in a 4x3 factorial scheme, the plot size was 2m(2) and the studied factors were: the application of efficient microorganisms (EM) in four levels: sin (0), seed inoculation at 100mL L-1 (S), foliar applications at 100mL L-1 (F) and the combination of seed inoculation with foliage applications (S + F) and three tomato varieties (Amalia, Rilia and Seen-2), with three replications. Were evaluated the fallowing indicators: the emergence percentage (%), stem diameter (cm), plant height (cm), number of leaves, yield (seedlings m(-2)) and the seedling production cycle (days). The results showed that, in the three tomato varieties, the combinate treatment of seeds inoculation with foliage applications of efficient microorganisms increased the stem diameter, plant height, number of leaves and yield in the Amalia and Rilia varieties by 26%, and Seen-2 by 25% with relation to the control and the seedling production cycle was reduced in Amalia and Seen-2 varieties by 24% and Rilia by 22%.
Keywords: biofertilizer; germination; foliage inoculation; interaction; yield; seed treatment